2023
DOI: 10.1002/aelm.202300235
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ionic Species on the Performance of Pedot:PSS‐Based Organic Electrochemical Transistors

Renan Colucci,
Bianca de Andrade Feitosa,
Gregório Couto Faria

Abstract: The organic electrochemical transistor (OECT) has received considerable interest in the field of bioelectronics due to its ability to support both ionic and electronic transport. However, the fundamental aspects of the OECT's operation are not yet fully understood. Here, the impact on the performance of poly(3,4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)‐based OECTs, of a series electrolytes with chloride‐based ions is evaluated, varying their cation counterpart under the extension of the Hofmei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Hydrogels of PEDOT:PSS have been made from its colloidal dispersions (1.1 -1.3 wt%) by mixing with ionic liquids (IL) and allowing to gel with time at room or elevated temperatures 42,43 . Ionic liquids induce gelation by performing charge screening of PEDOT and PSS, thereby promoting structural rearrangement of PEDOT and the formation of physical cross-links including through π-π stacking 44 . Our previous work has shown that specific concentrations of ionic liquid (>10 mg/mL) result in mixtures which transition from liquid to gel on a timescale of minutes to hours 42 .…”
Section: Formulation Of Pedot:pss Weak Gel Inks For Extrusion 3d Prin...mentioning
confidence: 99%
“…Hydrogels of PEDOT:PSS have been made from its colloidal dispersions (1.1 -1.3 wt%) by mixing with ionic liquids (IL) and allowing to gel with time at room or elevated temperatures 42,43 . Ionic liquids induce gelation by performing charge screening of PEDOT and PSS, thereby promoting structural rearrangement of PEDOT and the formation of physical cross-links including through π-π stacking 44 . Our previous work has shown that specific concentrations of ionic liquid (>10 mg/mL) result in mixtures which transition from liquid to gel on a timescale of minutes to hours 42 .…”
Section: Formulation Of Pedot:pss Weak Gel Inks For Extrusion 3d Prin...mentioning
confidence: 99%